Survei Keberadaan Hama Pada Tanaman Kacang Panjang (Vigna sinensis L.) Di Dusun Abe Pantai Kelurahan Asano Distrik Abepura Kota Jayapura - Gomies, Batseba (AGRICOLA, 2022)
This research aimed to find pests' presence and identify the types of pests that attack long bean plants and the symptoms of attack seen on plants in Abe Pantai Hamlet, Asano Village, Abepura District, Jayapura City. The method used in this research is a descriptive method with a survey research approach. In this survey, three kinds of data collection techniques were carried out: Interview, Observation, and Literature Study. Observations were made to determine the main types of pests that attack long bean plants in each experimental unit. The types of pests observed will be divided into three groups, namely: 1) Pests that attack plants in the morning (06.00 – 08.00); 2) Pests that attack plants during the day (11.00 – 13.00); 3) Pests that attack plants in the afternoon (16.00 – 18.00). All observations were made two times, namely two days of observation, with the distance between the first and second observations being seven days. The observation target was on plant parts that were suspected of being attacked, namely leaves, petioles, stems and long bean pods. The results of this study showed that the pests found in the long bean plantation area in Abe Pantai hamlet, Abepura District, Jayapura City were nine types of pests, namely: grasshoppers, caterpillars, aphids, armyworms, koksi beetles, green ladybugs, flower caterpillars, leaf-rolling caterpillars and pod borer caterpillars of long bean plants.